Are two-dimensional measured frontal plane angles related to three-dimensional measured kinematic profiles during running?. (January 2018) - Dingenen, Bart; Staes, Filip F.; Santermans, Lieselot; Steurs, Lien; Eerdekens, Maarten; Geentjens, Jurre; Peers, Koen H.E.; Thysen, Maarten; Deschamps, Kevin
Abstract: Objectives: To investigate the temporal relationship between two-dimensional measured frontal plane joint angles and three-dimensional measured kinematic profiles during the stance phase of running, and to assess the intra- and intertester reliability of the two-dimensional angles. Design: Observational study. Setting: Research laboratory. Participants: Fifteen injury-free elite athletes. Main outcome measures: Contralateral pelvic drop (CPD), femoral adduction (FA), hip adduction (HA) and knee valgus (KV) were measured at the deepest landing position during midstance with two-dimensional video analysis during running. CPD, HA and knee abduction were measured continuously during the entire stance phase through three-dimensional motion analysis. One-dimensional statistical parametric mapping was used to examine the temporal relationships between the two-dimensional angles and three-dimensional kinematic profiles. In addition, intra-class correlation coefficients (ICC) were calculated to assess the intra- and intertester reliability of the two-dimensional angles. Results: Two-dimensional CPD, FA and HA were significantly related to the three-dimensional HA kinematic profile. Two-dimensional CPD was significantly related to the three-dimensional CPD kinematic profile. No significant relationship was found between two-dimensional KV and three-dimensional knee abduction. Excellent intra- and intertester reliability was found for the two-dimensional angles (ICC 0.90–0.99). Conclusions: These findings support implementing two-dimensional video analysis to evaluate CPD and HA during running. Highlights: 2D measured contralateral pelvic drop relates to 3D measured contralateral pelvic drop. 2D measured contralateral pelvic drop relates to 3D measured hip adduction. 2D measured femoral adduction relates to 3D measured hip adduction. 2D measured hip adduction relates to 3D measured hip adduction. Excellent intra- and intertester reliability was found for the 2D measured angles.